2019
DOI: 10.2298/tsci180816294k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of heat transfer at a rectangular channel with combined effect of nanofluids and swirling jets in a vehicle radiator

Abstract: The present study is focused on the numerical investigation of heat transfer from a heated surface by using swirling jets and nanofluids. Consequences of discrete Reynolds number, inlet configuration and types of nanofluids (pure water,and TiO 2 -H 2 O) were studied numerically on heat transfer and fluid-flow. As a base coolant Al 2 O 3 -H 2 O nanofluid was chosen for all parameters. So, a numerical analysis was done by using a k-ω turbulent model of PHOENICS CFD code. It is determined that increasing Reynolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Irrespective of the improved cooling capacity, the fundamental approach of using fins has become extinct due to an increase in the size of the radiator. The radiator is an essential element in any engine system as it is the fundamental component of the cooling system [1,6]. The efficiency of an automobile engine is measured on high fuel economy , low emissions along with the performance of the engine [7].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the improved cooling capacity, the fundamental approach of using fins has become extinct due to an increase in the size of the radiator. The radiator is an essential element in any engine system as it is the fundamental component of the cooling system [1,6]. The efficiency of an automobile engine is measured on high fuel economy , low emissions along with the performance of the engine [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies related to thermal conductivity (TC) [2][3][4][5], convective heat transfer (CHT) [6][7][8], and heat absorption rate [9] were reported with possibilities to use nanofluids in heat transfer applications. Heat transfer studies using numerical techniques have proved the possibilities of improving the heat transfer [10][11][12][13].Thermal conductivity is one of the property of a nanofluid which is essential for the evaluation of heat transfer coefficient under different flow condition and operating temperature. This property of fluid changes with the volume concentration, size of the nanoparticles and temperature of the nanofluid [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they found that the thermal resistance of the system decreased by 32.5% compared to the use of pure water. Kilic and Abdulvahitoglu [12] studied on numerical investigation of heat transfer with nanofluids and swirling jets in a vehicle radiator. As a base coolant Al 2 O 3 -H 2 O nanofluid was chosen for all parameters.…”
Section: Introductionmentioning
confidence: 99%